O PRONAF e o desenvolvimento da agricultura familiar do município de Flor da Serra do Sul/Pr - Farias, Fernando Rodrigo (2010)
The National Program to Strengthen Family Farm (PRONAF) has provided a new economic dynamic for the Brazilian family farming. This policy of financialization was an important moment in the history of Brazilian agrarian structure, especially regarding small farms, as it represented the possibility of overcoming the lack of credit, lived during the financial crisis of the 1980s and the 1990s, expanded the credit to this new clientele. In that sense, this study investigates the importance of the development of family farming in the city of Flor da Serra do Sul / PR, in the period 2000 to 2009. We try to show them new perspectives that have arisen with the PRONAF about economic growth, possibility of structural changes in the productive system, their political bases and changes in quality of life of farmers benefited. Furthermore, we identified and analyzed contradictions that prevent a more comprehensive and efficient action of program resources, with an indication for the need of a job whose scope to reach the postaccess to finance.